STUDI FENOMENOLOGI PENERAPAN PRINSIP PATIENT CENTERED CARE PADA SAAT PROSES RESUSITASI DI IGD RSUD SAIFUL ANWAR MALANG - Eva Marti* Sri Andarini** Retno Lestari*** (The Indonesian Journal of Health Science, 2016)
High capability and effective performance that was implemented on cardiacarrest resuscitation have not always been followed by emphatic and careful attitudefrom resuscitation team. A patient Centered Care (PCC) method could help medicalpersonel to understand the difficult situation on emergency unit so that thecomminication and the credibility can be shown simultaneously. The purpose ot thisresearch is to deeply explore the principal of PCC that was implemented on cardiacarrest resuscitation. This research was using qualitative design combine withinterpretive phenomenology that involved seven participants including five seniornurse and two doctor from PPDS emergency unit of Saiful Anwar hospital. Thetranscript, result of interview, was analyzed by qualitative analysis; initial codeswere generated by each statement of participans which then were interpreted as atheme. The output of the research identified 8 theme that described theimplementation of PCC on this cardiac arrest resuscitation, ie (1) respected thedignity of patiens and their family, (2) taken care of safety and satisfaction, (3) afamily support, (4) holism, treating KIE on critical situation, (5) giving the bestservice consistently, (6) keep team collaboration, (7) any difficulties that have beenfaced, (8) supplement factor. The implementation of PCC on cardiac arrestresuscitation modulated by resuscitation that need rapidness and preciseness, acondition when patiens was critial (coma) and whose family in depression. Theprincipal of PCC really need the involvement of resuscitation team and the familyof patiens.